The Hubungan Antara Stress Kerja dan Supportive Work Environment dengan Work Life Balance pada Sat. Samapta Polres Kudus - Eko Irwan Kusuma; Dhini Rama Dhania (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to examine the relationship between job stress and supportive work environment with work-life balance among members of the Sat. Samapta Polres Kudus. This topic is considered important due to the high-pressure nature of police work, unpredictable working hours, and mental demands that may disrupt the balance between work and personal life. The research employed a quantitative approach with a survey method, involving 84 police officers as respondents. Data were collected using three psychological scales: job stress scale, supportive work environment scale, and work-life balance scale. Data analysis utilized multiple linear regression and Pearson correlation. The results indicated no significant relationship between job stress or supportive work environment and work-life balance (p > 0.05). Thus, both major and minor hypotheses were rejected. Despite the non-significant results, this study underscores the need for a multidimensional organizational approach to support the psychological well-being of police personnel through comprehensive interventions.